Chemistry and Neurotrophic Activities of (–)-Talaumidin and Its Derivatives - Harada, Kenichi; Kubo, Miwa; Fukuyama, Yoshiyasu (Frontiers in Chemistry, 2020)
(−)-Talaumidin (1), a 2,5-biaryl-3,4-dimethyltetrahydrofuran lignan isolated from Aristolochia arcuata Masters, exhibits significant neurite-outgrowth promotion and neuroprotection in primary cultured rat cortical neurons and in NGF-differentiated PC12 cells. The first enantioselective total synthesis of 1 was achieved by a flexible and reliable synthetic pathway involving an Evans asymmetric aldol reaction, as well as a stereocontrolled hydroboration and Friedel−Crafts arylation, to construct the four contiguous chiral centers on the tetrahydrofuran (THF) ring of 1. In order to investigate the stereochemistry−activity relationship of 1, a systematic synthesis of all diastereomers of 1 was accomplished by applying the synthetic strategy used for natural product 1. The evaluation of neurite-outgrowth promotion by all of the synthesized diastereomers indicated that the (–)-(1S,2R,3S,4R)-isomer 1e was significantly more active than naturally occurring 1. Additionally, we established a synthetic methodology for talaumidin derivatives that could be used to prepare a variety of analogues in a few steps and on a large scale. The synthesized racemic analogue rac-1e (56a) exhibited neurite-outgrowth promoting activity in NGF-differentiated PC12 cells to the same degree as the optically active (–)-1e, revealing that a relative configuration bearing all-cis- substituents is important for potent neurotrophic activity, whilst the absolute configuration does not affect activity. Fourteen analogues based on (±)-56a were prepared via the same synthetic methodology. Among them, 56b with a methylenedioxy group on both benzene rings was found to exhibit the most significant neurite outgrowth promotion. In addition, 56a and 56b induced regeneration of the mouse optic nerve in vivo, and their activity was higher than that of talaumidin, as well as their in vitro measured activity. Furthermore, the structure−activity relationship of 56b indicated that the two benzene rings were essential structures, and that the methyl groups on the THF ring could enhance the neurotrophic activity. This result suggests that the two benzene rings of the talaumidin derivatives are essential structures for neurotrophic activity, while the two methyl groups on the THF ring can enhance neurite-outgrowth activity. Finally, it was observed that 1 and derivatives 56a and 56b exhibited potent regenerative activity in the injured mouse optic nerve in vivo.